Real and nominal wage adjustment in open economies - Anders Forslund; Nils Gottfries; Andreas Westermark (Center for Economic Studies and ifo Institute (CESifo), 2006)
How are wages set in an open economy? What role is played by demand pressure, international competition, and structural factors in the labour market? How important is nominal wage rigidity and exchange rate policy for the evolution of real wages and competitiveness? To answer these questions, we formulate a theoretical model of wage bargaining in an open economy and use it to derive a simple wage equation where all parameters have clear economic interpretations. We estimate the wage equation on data for aggregate manufacturing wages in Denmark, Finland, Norway, and Sweden from the mid 1960s to the mid 1990s.
Keywords: J31; F41; F33; E52; J64; J63; J51; 330; wage formation; efficiency wage; turnover; bargaining; rent sharing; nominal wage rigidity; exchange rate policy; competitiveness; Offene Volkswirtschaft; Reallohn; Lohnbildung; Lohnrigidität; Verhandlungsmacht; Gewerkschaft; Wechselkurs; Schätzung; Nordeuropa